ANALYSIS OF LANGUAGE STYLE IN TRILOGY NOVEL HUJAN BULAN JUNI BY SAPARDI DJOKO DAMONO - Asmiati, Asmiati; Hamsa, Akmal; Agussalim AJ, Andi; Amir, Djohar; Irmawati, Irmawati (JURNAL ILMU BUDAYA, 2023)
This research is qualitative research using Gorys Keraf's language style theory which aimed to; 1) Analyze the types of figurative language in the trilogy of the novel Hujan Bulan Juni by  Damono. 2) Analyzing the meaning of figurative language in the trilogy of Hujan Bulan Juni by Damono.  The data sources in this study were three books of the novel Hujan Bulan Juni trilogy. The data collection technique used is that used is the library, read, note-take. The results indicated that in the novel trilogy, Hujan Bulan Juni  used the language styles of Alliteration, Association, Anastrof, Apofasis or Preterisio, Apostrophe, Asindeton, Polisendeton, Chiasmus, Elipsis, Euphemismus, Litotes, Histeron Proteron, Pleonasm, and Tautology, Periphrasis, Prolepsis or anticipation, Erotesis or Rhetorical Question, Sylepsis, and Zeugma, Correction or Epanortosis, Heperbola, Paradox, Oxymoron. This was because Sapardi Djoko Damono created the best use of language to obtain the aesthetic effect of language.